Fast-Charging of Automotive Lithium-Ion Cells: In-Situ Lithium-Plating Detection and Comparison of Different Cell Designs. Issue 13 (14th September 2020) - Adam, A.; Wandt, J.; Knobbe, E.; Bauer, G.; Kwade, A.
Abstract : Fast-charging is a key requirement for customer acceptance of battery electric vehicles. In this work, various methods for lithium-plating detection are applied to prismatic hard-case lithium-ion cells to demonstrate their applicability for large-format automotive cells despite possible thermal and electrochemical inhomogeneities. Different fast-charging profiles with a charging time of less than 30 min from 10% to 80% state-of-charge are examined with methods based on coulombic efficiency, cell voltage analysis and swelling force. To validate these results, a lifetime cycling test with a subsequent cell opening is performed, followed by a discussion on lithium-plating detectability and the restrictions of each method. In order to further illustrate the applicability of the lithium-plating detection methods, the fast-charging ability of two cells with the same format but different cathode active materials, namely NMC622 and NMC811, are compared. Furthermore, a coupled electrochemical-thermal simulation is performed to study the effect of the cell design on the fast-charging ability and to elucidate why a higher cell energy density does not necessarily lead to a worse fast-charging ability.